1985
DOI: 10.1111/j.1570-7458.1985.tb03554.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of sieve element penetration by aphid stylets during electrical recording

Abstract: The probing activities of Brevicoryne brassicae (L.) on a host plant Brassica oleracea (L.) were electronically monitored using a direct current (DC) device. Two electrical penetration graphs are described, including a pattern, D + E, at two different potential levels; the normal level of pattern C, D + E(c), and the potential drop level, D+E(pd). Stylets were amputated during these patterns, sap exudation from the stumps was scored, and the penetrated leaf area with the remnants of the stylets were processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 24 publications
(30 reference statements)
2
71
0
3
Order By: Relevance
“…No callose is shown in punctured sieve elements, neither in necrotic cells nor in those that survived. Evert et al (1973) and Kimmins & Tjallingii (1985) also found no callose in sieve elements containing stylet tips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No callose is shown in punctured sieve elements, neither in necrotic cells nor in those that survived. Evert et al (1973) and Kimmins & Tjallingii (1985) also found no callose in sieve elements containing stylet tips.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous stylectomy during waveform E2 (Kimmins & Tjallingii, 1985;unpublished data), the stylet tips of probe A were located in a sieve element (Fig. 6).…”
Section: Stylet Tips In Sieve Elementmentioning
confidence: 94%
See 1 more Smart Citation
“…After amplification, these voltage fluctuations are recorded as the EPG signal. Evidence supporting the correlation between electrical waveforms and different elements of the penetration behaviour of aphids feeding on soft plant tissues (unlignified tissues) has been reported (Kimmins & Tjallingii 1985;Spiller et al 1985;Tjallingii 1987;Tjallingii & Hogen Esch 1993). The EPG waveforms are characterised in terms of amplitude, frequency, and voltage level (van Helden & Tjallingii 2000).…”
Section: H02093; Published 12 June 2003 Received 27 November 2002 Acmentioning
confidence: 99%
“…Sampling of phloem sap from individual STs can also be achieved using aphid stylectomy (Fisher and Frame, 1984). Aphids feed exclusively from the phloem (for review, see Will and van Bel, 2006), and a large literature shows that their stylet bundles penetrate and extract phloem sap from an individual ST (Kimmins and Tjallingii, 1985;Tjallingii and Esch, 1993). It is possible to sever the stylets of feeding aphids and collect samples of phloem sap (Unwin, 1978;Pritchard, 1996;Zhu et al, 2005), and studies have confirmed that the samples obtained represent pure ST sap (Tjallingii and Esch, 1993).…”
mentioning
confidence: 99%